Mindfulness-based body scan training in multimodal physiotherapy for vulvodynia – a randomized controlled feasibility study - Heidi Halbedl; Daniela Melitta Pfabigan; Irene Ebhardt; Gerda Trutnovsky (Journal of Psychosomatic Obstetrics and Gynecology, 2025)
This randomized controlled trial explored the feasibility and preliminary effectiveness of integrating mindfulness-based body scan (MBBS) interventions into multimodal pelvic floor physiotherapy for vulvodynia treatment. Participants received ten sessions of standardized physiotherapy. The mindfulness intervention group was instructed to additionally perform home-based audio-file guided MBBS five times a week. The primary study endpoint was feasibility. The effect on pain intensity, pain characteristics and sexuality were assessed with Numeric Rating scales (NRS), the McGill-Melzack Pain Questionnaire (MPQ), the Female Sexual Distress Scale (FSDS) and Female Sexual Function Index (FSFI) and digital assessment of pelvic floor. Thirty-three women were randomized and completed the end-of-treatment assessments and 26 (79%) attended the follow-up. 15 of 17 participants of the intervention group (88%) performed the body scans more than ten times and the feasibility criteria were achieved. The intervention group showed significantly better improvements in NRS of average pain, MPQ subscales and FSDS total score. Pelvic floor assessment showed a significant improvement of myofascial pressure points over time with no difference between study groups. Integration of MBBS trainings into multimodal pelvic floor physiotherapy for vulvodynia is feasible and well accepted and may improve pain reduction and sexual function.